Introgression of Black Rot Resistance from Brassica carinata to Cauliflower (Brassica oleracea botrytis Group) through Embryo Rescue - Sharma, Brij B.; Kalia, Pritam; Singh, Dinesh; Sharma, Tilak R. (Frontiers in Plant Science, 2017)
Black rot caused by Xanthomonas campestris pv. campestris (Xcc) is a very important disease of cauliflower (Brassica oleracea botrytis group) resulting into 10-50% yield losses every year. Since there is a dearth of availability of resistance to black rot disease in B. oleracea (C genome), therefore exploration of A and B genomes was inevitable as they have been reported to be potential reservoirs of gene(s) for resistance to black rot. To utilize these sources, interspecific hybrid and backcross progeny (B1) were generated between cauliflower ‘Pusa Sharad’ and Ethiopian mustard ‘NPC-9’ employing in vitro embryo rescue technique. Direct ovule culture method was better than siliqua culture under different temperature regime periods. Hybridity testing of F1 inter-specific plants was carried out using co-dominant SSR marker and Brassica B and C genome-specific (DB and DC) primers. Meiosis in the di-genomic (BCC) interspecific hybrid of B. oleracea botrytis group (2n = 18, CC) × B. carinata (2n = 4x = 34, BBCC) was higly disorganised and cytological analysis of pollen mother cells revealed chromosomes 2n = 26 at metaphase-I. Fertile giant pollen grain formation was observed frequently in interspecific F1 hybrid and BC1 plants. The F1 inter-specific plants were found to be resistant to Xcc race 1. Segregation distortion was observed in BC1 generation for black rot resistance and different morphological traits. The At1g70610 marker analysis confirmed successful introgression of black rot resistance in interspecific BC1 population. This effort will go a long way in pyramiding gene(s) for resistance against black rot in Cole crops, especially cauliflower and cabbage for developing durable resistance, thus minimize dependency on bactericides.